The Principles of the Welfare Law State in an Islamic Perspective - Sri Kusriyah (Jurnal Daulat Hukum, 2022)
The principles of a welfare state are a choice of state system in most countries in the world. Islam as a religion for all mankind and mercy for the natural environment, has principles on how to regulate the state so that it can provide benefits for human life, this paper aims to find out how the principles of a welfare state and an Islamic perspective. The method used in this paper uses normative juridical methods, the data required is in the form of secondary data with technical data analysis using qualitative analysis. The results of the discussion show that Islam as a teaching has the principle that the people have the right to welfare, and the state/government is obliged to promote welfare, educate the people's lives, and must even be active in all aspects of life towards the welfare of its citizens a. Freedom from poverty, b. freedom to choose a lawful job, c. property rights function socially, d. the right to education, e. the right to welfare. The principle of welfare in Islam is directed to achieve the system. a. The system of Islamic society is a system of social life that is advanced, mobile and active, capable enough to build a modern and advanced society, b. The Islamic social system with its recognition of the five human rights and legislation for social security, has the power to eradicate poverty, stupidity, cowardice and inferiority complex, c. The Islamic social system is suitable for all Muslims and non-Muslims, because the basics and rights according to this system are equally distributed to all residents without exception, d. The Islamic community system includes the people and the government in implementing social security, e. The Islamic society system is easy to form, not rigid, can be practiced at any time in accordance with the times and the movement of progress.